Wireless thin layer force sensor based on a magnetostrictive composite material. (16th May 2017) - Adelsberg, Nehara; Weber, Yarden; Yoffe, Alexander; Shilo, Doron
Abstract: Magnetostrictive composites are of considerable interest for real-time remote force sensing and structural health monitoring. In this study, we produced wireless thin-layer force sensors based on washers made of magnetostrictive composite materials featuring terfenol-D particles embedded in an epoxy matrix. The magnetostrictive composite materials were characterized by a combination of characterization techniques, including x-ray diffraction, magnetic hysteresis measurements, and dedicated magneto-mechanical tests. We demonstrated an operation range over which the magneto-mechanical response is linear, repeatable, has a minor amount of hysteresis and demonstrates no relaxation or rate effects. In addition, we demonstrated ways for producing force sensors with a higher sensitivity and signal-to-noise ratio by increasing the poling magnetic field and the temperature during the curing of the epoxy. Moreover, we identified the sequence of processes that occur during the curing and poling stage and the critical (hardest) process that eventually determines sensor sensitivity.